Dyskurs podręcznikowy a dyskurs dziecięcy – odmienne postrzeganie rzeczywistości - Aleksandra Szyller (Problemy Wczesnej Edukacji)
Textbooks have become a source of assistance that settled for good into Polish education landscape, a measure without which many adults cannot imagine the school reality. At the same time, the lack of the comprehensive studies on education packs is noticeable. What is more, the voice of children in Poland is marginalized or completely ignored, as opposed to the Western countries. The perspective of the youngest participants of the education process, who are the direct recipients of the textbook offer and are critical and thoughtful, is very rarely taken into account. Whereas their opinions may be a source of very powerful changes in education.